Band-pass filter based on complementary split ring resonator - Badr Nasiri; Abdelhadi Ennajih; Ahmed Errkik; Jamal Zbitou; Mounir Derri (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2020)
This letter presents a new circuit of the band-pass filter designed by using microstrip technology. Based on complementary split ring resonator and various series of optimization technic and a specific design method, a miniature band-pass filter with excellent electrical performances is achieved. First of all, the metamaterial unit cell is studied to obtain a desired resonant frequency and it is implemented in the ground plan in order to increase the characteristics of the bandpass behavior and decrease its operating frequencies. This proposed circuit is designed on an FR-4 substrate having a relative permittivity of 4.4 tangential losses of 0.025 and thickness of 1.6 mm. This filter is developed by using CST Microwave. The obtained features allow this filter to be used in diverse wireless applications such as IMT-E and WiMax.